The Effect of the Formal Organizer Strategy in Acquiring Islamic Concepts among Fifth Class Students and Developing Their Visual Thinking - ALJabouri, Maad Saleh Fayyad; Shehab Al Nuaimi, Juhayna Turki (Journal of Tikrit University for Humanities, 2020)
The current research aims to identify (the effect of the formal organizer's strategy on acquiring Islamic concepts among fifth-class students and developing their visual thinking). To achieve the objectives of the research, hypotheses were formulated subject to experimentation. The researcher used the experimental design with two equal groups. The research sample consisted of (64) female students of the fifth scientific bio-science. They were divided into two group. The first group consisted of (32) students for the experimental group. The second group consisted of (32) students for the control group. When the researcher compared between the two research groups in the following variables: age calculated by months, the grades of the total female students in the previous year, the grades of female students in the subject of the Glorious Qur’an and Islamic education for the previous year, the Raven test of intelligence, the academic achievement of the parents, and the pre-test of the two research groups in thinking Optical. The researcher applied the pre-test and post-test for visual thinking and after statistically processing the data using the T-test for two independent samples. The results showed that there is a statistically significant difference between the average degrees of the post-test for visual thinking among the students of the experimental group that studied using the strategy (formal organizer) and students of the control group who studied the subject using the traditional method.